Emergency Hartmann´s procedure: short term outcomes in the old and the very old - Rocha, R (2014)
Objectives: Emergency Hartmann´s procedure is associated with significant morbidity and mortality, particularly in the elderly populations. Our aim is to compare the short term outcomes of old [65-80 years old[ and very old patients (80 or more) submitted to this procedure. Materials: Between January 2008 and December 2012 we submitted to emergency Hartmann´s procedure 105 patients: 65 old and 40 very old. We retrospectively reviewed patient charts and comparatively analysed demographic data, indications to surgery, P-POSSUM, ASA, intensive care unit stay, medical and surgical morbidity and 30-day mortality and performed univariate and multivariate logistic regression analysis. Results: x female, years . Comparing the Old and Very Old groups - Neoplasia (41% vs 47,5%), Acute Diverticulitis (31% vs 22,5%); 30-day mortality rate of 10% vs 45% (p value<0,05). Conclusions: Very old age was an independent factor of morbidity and mortality in emergency Hartmann´s procedure in our patients.